Comparison of Sarcopenia Diagnostic Component Between Two Age Groups in Men - Yahya Taqiuddin Robbani; Novira Widajanti; Nuniek Nugraheni Sulistiawaty (Health Notions, 2020)
Sarcopenia is a condition which characterized by loss of muscle mass, muscle strength and muscle function due to aging. Some study found that sarcopenia prevalence was more common in men than women. This study aims to determine the comparison of sarcopenia diagnostic component between two group ages in men by observing and comparing muscle mass, handgrip strength and usual gait speed according to Asian Working Group on Sarcopenia (AWGS) diagnostic criteria that analyzed by Independent Sample T Test. The sample size with consecutive sampling technique was 149 mens which divided into two groups based on ages of elderly over 60 years (n = 73) and young adult between 18-40 years (n = 76). From the independent sample t test results, there was significant difference of muscle mass mean, handgrip strength mean and gait speed mean between elderly group and young adult group by 2.467 (SD ± 0.1454) kg/m2 (t(98.350) = -16.969; p = 0.000), 10.455 (SD ± 1.0983) kg (t(147) = -9.519; p = 0.000) and 0.4753 (SD ± 0.2808) m/s (t(11.636) = -16.747; p = 0.000) which means along with increasing age, sarcopenia diagnostic components value, i.e. muscle mass, muscle strength, and physical performance will also decrease. Keywords: sarcopenia; bioelectric impedance analysis; handgrip strength; gait speed; AWGS